RPAS DATA TRANSMISSION VIA GROUND NETWORK - Grekhov, Andrii; Kondratiuk, Vasyl; Ilnytska, Svitlana (Proceedings of National Aviation University, 2020)
First built RPAS communication channel models including ground network was created, the dependencies of channel’s average utilization on the transaction size with various statistical distribution laws for the time between transactions were analyzed. Communication links with different bandwidths were investigated, the influence of the bit error rate and the packet fail chance on the communication channel utilization were studied. The results indicate that the most preferable for data transmission is LogNormal distribution law. Data transmission over a line-of-sight RPAS communication channel and over terrestrial network (beyond-line-of-sight) was compared for the first time.